Prenatal development of dew claws in buffalo: A histomorphochemical study - BANSAL, NEELAM; UPPAL, VARINDER; ANURADHA, ANURADHA (The Indian Journal of Animal Sciences, 2015)
The present study was conducted on 12 buffalo foetii obtained from slaughter house. The curved crown rump length (CVRL) of all the foetii was measured and their age was estimated in days. The dew claws of forelimb and hind limb were fixed in 10% neutral buffered formalin and processed by acetone-benzene schedule. The paraffin sections of 5–7 μm thickness were cut and stained with Hematoxylin and Eosin, Masson’s trichrome, Periodic acid Schiff, alcian blue and bromphenol blue stains. At 10.0 cm CVRL, the claws comprised mesenchymal cells covered by thin epidermis with varying thickness. With advancing age at 18.0 cm CVRL, their wall was composed of 2 layers of cuboidal cells covered by a thin cornified cell layer. In 28.1 cm CVRL foetus, it was made up of stratum externum, stratum medium, stratum internum, corium and rudimentary phalanx. The stratum internum consisted of a single layer of basal cells with elongated nuclei, which rested upon the basement membrane. The epidermis of dew claws consisted of a single layer of stratum basale, 1–2 layers of stratum spinosum cells, 1–2 layers of stratum granulosum cells and an overlying keratinized layer. The corium was observed between horny lamellae of stratum internum and spongy bone. It contained collagen, reticular and elastic fibers with large number of blood vessels. At 45.5 cm CVRL, the stratum internum was made up of lamellae extending inward from stratum medium. These lamellae appeared as finger like projections at this stage and became branched at 60 cm CVRL onwards. The primary and secondary branches were also observed with the advancement of foetal age. Histochemical study revealed a moderate to strong reaction for acid and neutral mucopolysaccharides and basic proteins.